ANALYSIS OF AFLATOXIN M1 IN RAW MILK OF DAIRY FARMS IN AREQUIPA - Ortiz Z., César (2009)
The aim of the present study was to evaluate the presence of aflatoxin M 1 in raw milk samples from dairy farms of Arequipa milkshed. Milk samples were collected from 10 dairy farms located in the irrigated area of Majes, Santa Rita, La Joya and Lluta districts in two seasons (summer and winter) of 2008. Milk farms were classified as intensive and semintensive according to their productive system. Zero positive milk samples were obtained during the study and therefore, it is concluded that aflatoxin M1 is not a contaminant of fresh milk in the region.